ANALISIS INVESTASI TERHADAP PERKIRAAN BIAYA PENAMBANGAN BATUBARA SWAKELOLA DI PT. INDOMINCO MANDIRI - Screendary , Yuddy
Mining activities are profit-oriented, therefore production should be maximized with minimal cost. At present the coal mining in PT. Indominco Mandiri is perform by a contractor PT. Pama Persada Nusantara. As aforementioned, one of the efforts to minimize cost is by doing the self-managing mining. The reduction of cost can be made if the estimated self-managing coal mining cost is lower than that offered by the contractor. The self-managing coal mining cost includes owning and operating cost, investment of additional infrastructure and additional general and administrative cost. The deduction of self-managing coal mining cost toward the cost of coal mining by the contractor are US (dollar) 26,00/hectar or 3,25% for land clearing and top soil movement, US (dollar) 0,35/bcm or 25,74% for stripping of overburden, US (dollar) 0,05/ton or 3,01% for coal mining and US (dollar) 2,331ton or 63,32% for coal transportation from mine stockyard to port stockyard. The result of the calculation shows that the cost of self-managing coal mining is cheaper than the cost of coal mining by the contractor. The investment analysis on the 2,50%/annum of coars selling price increase, causes net present value negative, internal rate of return is less than 10,00%, benefit cost ratio is less than 1,00 and payback period is more than 20,00 years. While that on the 5,00%lannum of coals selling price increase, causes positive net present value, internal rate of return is more than 10,00%, benefit cost ratio is more than 1,00 and payback period is less than 20,00 years. The result of the investment analysis shows that the increase of coals selling price significantly affects the worthiness of coal mining, because the higher percentage of the increase of coals selling price (5%,00lannum or more) is the higher worthiness of the mining is, whereas when the increase of coals selling price is small (2,50%/annum) the coal mining will suffer losses.